Multirate Optical CDMA Systems Combining Generalized Modified Prime Sequence Code and Bi-Orthogonal Code - Ono, Kyohei; Matsushima, Tomoko K.; Yamasaki, Shoichiro; Tanaka, Hirokazu (IEEE access, 2024)
Recently, visible light communications (VLCs) have attracted attention as a complement to wireless communications by radio frequency. In addition, the demand for Internet of Things (IoT) communications has increased in the last decade, and VLC-based IoT systems are being considered. Because IoT devices operate at various data rates, multirate transmission is required. Herein, we propose a scheme that supports multirate data transmission for synchronous optical code division multiple access systems. This scheme employs a generalized modified prime sequence code and multiple extended bi-orthogonal codes. The proposed scheme realizes multirate transmission with an arbitrary number of data rate levels by superimposing spreading codes of different codelengths. In addition, the proposed scheme eliminates not only interference between users with the same data rate, but also interference between users with different data rates. Furthermore, we investigated the bit error rate performance and energy efficiency of the proposed scheme, considering the effects of background light, dark current, and PIN photodiode noise including shot noise, and thermal noise.